(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article analyzes the Orenburg Muftiyat’s activity, which is based by the tsarist Russia in the period between the end of XVIII century and the middle of XIX. This period has a great importance and role in analyzing the Muslim management in the territory of Kazakhstan. In this period, there was a lot of socio-political changes. The Orenburg Muftiyat was a main structure, which had to ensure that all changes implemented by the tsarist authority are executed. Despite a huge role of the Orenburg Muftiyat, there was a few researches dedicated to its activity in the context of socio-political changes in the Kazakh society. In researching this topic, some reasons behind establishing the Orenburg Muftiyat by the tsarist authority have been pointed. Investigating the Orenburg Muftiyat’s activity, the author demonstrates how Muslim nations, particularly Kazakhs, have adopted step-by-step to the system of administrative management of Russian Empire. Thanks to historico-logical method, the positive and negative factors of model of Muslim managment system in the tsarist Russian, which influenced the Kazakh society, hasbeen considered. It has been proved that the requirements of selection of clergy by the Muftiyat, stipulated by the tsarist authority, had a positive influence on the development of Hanafi school in the Kazakh society. However, it should be noticed, that the authority in some degree has restricted the activity of some clergies. Despite a fact that the Russian Empire has paid a lot of attention to Orthodox Christianity, it also has developed the system of Muslim management. As a result, adoption of Muslims, subordinated to the Empire, to the secular system of management has been increased. There is a need of a comprehensive study of this topic and a need to qualify the terminology this regard. Key words: Orenburg Muftiyat, Islam, tsarist Russia, clergy, mufti.